2010
DOI: 10.1186/1471-2393-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers in the humanization of childbirth practice in Japan

Abstract: BackgroundHumanizing birth means considering women's values, beliefs, and feelings and respecting their dignity and autonomy during the birthing process. Reducing over-medicalized childbirths, empowering women and the use of evidence-based maternity practice are strategies that promote humanized birth. Nevertheless, the territory of birth and its socio-cultural values and beliefs concerning child bearing can deeply affect birthing practices. The present study aims to explore the Japanese child birthing experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 22 publications
1
123
1
9
Order By: Relevance
“…[50,5254] Some midwives expressed similar concerns where midwifery confidence, skills and support were low within specific organisations [46,50,5254] and systems. [46,47,49,5254] As explained by this midwife in Chile, “ Neither midwives nor women are empowered enough to question a medical prescription . ” ( [49]: p.1153).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50,5254] Some midwives expressed similar concerns where midwifery confidence, skills and support were low within specific organisations [46,50,5254] and systems. [46,47,49,5254] As explained by this midwife in Chile, “ Neither midwives nor women are empowered enough to question a medical prescription . ” ( [49]: p.1153).…”
Section: Resultsmentioning
confidence: 99%
“…[27,36,4244,46,47,55] This could simply be a consequence of different financing structures, clinical policies, and the working environment. However, it could also be due to the power of the predominant philosophy of pregnancy and childbirth, based on perceptions of the purpose of the particular kind of unit.…”
Section: Resultsmentioning
confidence: 99%
“…It can be difficult to implement continuous support during childbirth if this practice is not specifically mentioned in policies and guidelines. According to Behruzi et al (2010), the most important barriers identified in providing humanised birth care (including continuous support) were institutional rules and strategies that restricted the presence of birth companions.…”
Section: Category 2: Policies and Guidelinesmentioning
confidence: 99%
“…En Japón, la principal barrera identificada son las reglas institucionales que limitan la presencia de un compañero en el parto (21) , mientras que en el Reino Unido, ha sido el uso inapropiado de la tecnología sin tener en cuenta el nivel de riesgo de las mujeres, la falta de preparación médica en el parto normal y los bajos niveles de dotación de personal (22) . Una Cohorte, realizada en un hospital sueco, demuestra que en gestantes de bajo riesgo si se reducen los procedimientos obstétricos durante el parto no se pone en peligro la salud materno-infantil y los resultados son mejores, como menor índice de cesáreas urgentes, menor número de partos instrumentados, menor necesidad de uso de analgesia epidural y menor índice de distrés respiratorio fetal (23) .…”
Section: Dimensión De La Calidad Técnica O Calidad Del Producto Sanitunclassified